Peru : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Peru has successfully navigated the commodity cycle and the 2008-09 global financial crisis, and still leads growth among large Latin American economies. Following a sharp and unexpected drop in 2014, growth picked up in 2015, reaching 3.3 percent largely owing to higher metals production and fishing, and a partial recovery in services and commerce. Peru is now positioned to grow faster in the next two years, as mining production reaches full capacity and large infrastructure projects advance. Inflation is expected to decline. Risks to the outlook are balanced, and downside risks are mostly on the external side.